2013
DOI: 10.1145/2442087.2442095
|View full text |Cite
|
Sign up to set email alerts
|

Achieving autonomous power management using reinforcement learning

Abstract: System level power management must consider the uncertainty and variability that come from the environment, the application and the hardware. A robust power management technique must be able to learn the optimal decision from past events and improve itself as the environment changes. This article presents a novel on-line power management technique based on model-free constrained reinforcement learning (Q-learning). The proposed learning algorithm requires no prior information of the workload and dynamically ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 34 publications
0
71
0
Order By: Relevance
“…The advantage our approach employing EPD (2) during initial learning (i.e., RL step), is illustrated in Table II, highlighting the average number of explorations for three applications compared against an existing approach [21]. It can be observed that our approach benefits from reduced exploration due to the relationship between current performance and the V-F action (4) [21].…”
Section: Number Of Explorationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The advantage our approach employing EPD (2) during initial learning (i.e., RL step), is illustrated in Table II, highlighting the average number of explorations for three applications compared against an existing approach [21]. It can be observed that our approach benefits from reduced exploration due to the relationship between current performance and the V-F action (4) [21].…”
Section: Number Of Explorationsmentioning
confidence: 99%
“…Predicting the state of the system is a key step in RL and in our methodology the expected workload is classified into a system state at the beginning of each decision epoch [8], [9]. The state of the system is represented using the CPU Cycle Count (CC), obtained using the performance monitoring unit.…”
Section: A State Prediction and Q-tablementioning
confidence: 99%
See 2 more Smart Citations
“…RESULTS The proposed run-time approach is validated on Texas Instrument's PandaBoard featuring ARM A9 cores and Intel quad-core system running Linux. The proposed approach is compared with one representative approach from each category of related works -the reinforcement learning-based technique of [4], the prediction-based DVFS technique of [1] and the multinomial logistic regression-based technique of [9].…”
Section: B Parameter Fixingmentioning
confidence: 99%